The theory and practice of investment management : asset allocation, valuation, portfolio construction, and strategies - Fabozzi, Frank J.; Markowitz, H. (Harry), 1927- (Hoboken, N.J. : John Wiley & Sons, 2011)
"An updated guide to the theory and practice of investment management Many books focus on the theory of investment management and leave the details of the implementation of the theory up to you. This book illustrates how theory is applied in practice while stressing the importance of the portfolio construction process. The Second Edition of The Theory and Practice of Investment Management is the ultimate guide to understanding the various aspects of investment management and investment vehicles. Tying together theoretical advances in investment management with actual practical applications, this book gives you a unique opportunity to use proven investment management techniques to protect and grow a portfolio under many different circumstances. Contains new material on the latest tools and strategies for both equity and fixed income portfolio management Includes key take-aways as well as study questions at the conclusion of each chapter A timely updated guide to an important topic in today's investment world This comprehensive investment management resource combines real-world financial knowledge with investment management theory to provide you with the practical guidance needed to succeed within the investment management arena."--Provided by publisher.
pt. 1. Instruments, asset allocation, portfolio selection, and asset pricing -- pt. 2. Equity analysis and portfolio management -- pt. 3. Bond analysis and portfolio management.
Print version record.
Keywords: Business enterprises -- Finance; Investments; Business; Portfolio management; Investments; Business enterprises -- Finance; BUSINESS & ECONOMICS -- Investments & Securities -- General; Business enterprises -- Finance; Investments; Portfolio management; Investments; Business enterprises / Finance; Electronic books